DESIGN AND IMPLELMENTATION A PC BASED SYSTEM FOR CIRCUIT TESTING (Journal of Engineering, 2008)
This thesis deals with design and implementation of PC based control unit for testing systems. The design of the system involves mainly the hardware circuits, and software. The tester carries out the following types of test Analog circuit test, Digital I.C. test, Incircuit test, and functional test. The system designed and implemented, the implemented system hardware was built around two parallel ports. The hardware includes four buffers used as IØ channels addressed as Analog input (A\I), Analog output (AØ), Digital input (D\I), and Digital output (DØ). The system also includes Analog to digital converter, Digital to analog converter, and resistor testing circuit. The data to processed can be in digital or in an analog form. In the same time the hardware outputs controlling signals for testing and controlling the equipments. These signals are in digital or analog form. The implemented system software has two main user interfaces, one for selecting the mode of operation (as read or write), and activates the associated buffer. The other which included the functions of tests. For the resistor testing, I.C. testing, and circuit testing the system software compares inputs from the unit under test (UUT) with stored upper and lower limits, if the input is a value between them the test is considered successful otherwise the test fails.The software has been written in "Visual Basic" programming language running under windows® (ME\XP) operating system environment and tested on the already exist hardware. The system has been tested and it worked successfully for different resistance value and different types of Digital I.C.